2005
DOI: 10.1159/000081793
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Angiotensin II with Losartan Attenuates Transforming Growth Factor-β1 Inducible Gene-h3 (βig-h3) Expression in a Model of Chronic Cyclosporine Nephrotoxicity

Abstract: Background: We recently demonstrated that upregulation of the transforming growth factor (TGF)-β1 inducible gene-h3 (βig-h3) is associated with tubulointerstitial fibrosis (TIF) in a rat model of chronic cyclosporine A (CsA) nephrotoxicity. This study investigated the association between βig-h3 expression and TIF during losartan treatment in this model. Methods: Adult Sprague-Dawley rats kept on a salt-depleted diet (0.05% sodium) were treated daily for 4 weeks with vehicle (olive oil, 1 ml/kg), CsA (15 mg/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…It is well known that TGF-β1 is implicated in the fibrosis of chronic CsA nephropathy [10], and along with others we have delineated that βig-h3 expression serves as an index of TGF-β1 bioactivity [30, 31, 40]. In the present study, we found that rHuEPO decreased interstitial fibrosis, and this was paralleled with suppressed TGF-β1 and βig-h3 expression, and this suppression was more pronounced at 4 weeks.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It is well known that TGF-β1 is implicated in the fibrosis of chronic CsA nephropathy [10], and along with others we have delineated that βig-h3 expression serves as an index of TGF-β1 bioactivity [30, 31, 40]. In the present study, we found that rHuEPO decreased interstitial fibrosis, and this was paralleled with suppressed TGF-β1 and βig-h3 expression, and this suppression was more pronounced at 4 weeks.…”
Section: Discussionsupporting
confidence: 84%
“…For coloration, sections were incubated with a mixture of 0.05% 3,3′-diaminobenzidine containing 0.01% H 2 O 2 at room temperature until a brown color was visible, washed with TBS, counterstained with hematoxylin and examined under a light microscope. The procedure of immunostaining for ED-1 (Serotec Inc., UK), C-reactive protein (CRP, Sigma) , EPO, EPOR, proliferating cell nuclear antigen (PCNA, Dako A/S, Denmark), and TGF-β1-inducible gene-h3 (βig-h3) [30, 31] was similar to that for OPN. The number of PCNA-, ED-1-, and CRP-positive cells was autocounted using a digital camera-based image analyzer at twenty different fields in each section under ×200 magnification.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of ACE inhibitors (ACEIs) and angiotensin II receptor blockers (ARBs) on CNI nephrotoxicity have been studied extensively. In rats, it was shown that ACEIs and ARBs can prevent cyclosporineinduced interstitial fibrosis and improve renal function (145,(357)(358)(359). Also, in humans, ACE inhibition reduced CNI nephrotoxicity associated with cyclosporine use (360) and improved alterations of the cardiovascular system generally observed in renal transplant patients (361).…”
Section: Other Approachesmentioning
confidence: 99%
“…Based on these observations, ANG II production has been regarded as a key event of inflammation in the heart, vessels and kidney, and therefore it has been considered as a therapeutic target [9]. In this way, inhibitors of ANG II synthesis and/or AT1 and AT2 receptor antagonists improved renal function [10]. …”
Section: Introductionmentioning
confidence: 99%